Enantiomeric resolution and docking studies of chiral xanthonic derivatives on chirobiotic columns - Phyo Y.Z. (2018)
A systematic study of enantioresolution of a library of xanthonic derivatives, prepared “in-house”, was successfully carried out with four commercially available macrocyclic glycopeptide-based columns, namely ChirobioticTM T, ChirobioticTM R, ChirobioticTM V and ChirobioticTM TAG. Evaluation was conducted in multimodal elution conditions: normal-phase, polar organic, polar ionic and reversed-phase. The effects of the mobile phase composition, the percentage of organic modifier, the pH of the mobile phase, the nature and concentration of different mobile phase additives on the chromatographic parameters are discussed. ChirobioticTM T and ChirobioticTM V, under normal-phase and reversed-phase modes, respectively, presented the best chromatographic parameters. Considering the importance of understanding the chiral recognition mechanisms associated with the chromatographic enantioresolution, and the scarce data available for macrocyclic glycopeptide-based columns, computational studies by molecular docking were also carried out. 2018 by the authors.